Alternatif Pengembangan Kecamatan Sape Sebagai Pusat Kegiatan di Bagian Timur Kabupaten Bima, NTB - Azzahra, Siti Fatimah; Ma'rif, Samsul (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Since the reign of Bima district split into two autonomous regions that become Bima and Bima City, the issue of the transfer of the district capital began to sound so as to make a few districts in Bima start to straighten the sake elected to the district capital. One of them is the District of Sape. District Sape, a district that has a lot of potential, location of districts Sape is located in the eastern part of the district of Bima make it as a gateway economy either from or to a province adjacent namely NTT, besides the presence of the port sape straits sape as a transportation hub of and to the Bima-Labuan Bajo East Nusa Tenggara province, making it the heart activity activity Center to provincial or national. From many of the above considerations may be raised several alternative selected as appropriate for the development of districts Sape. With the method used is descriptive Qualitative analysis assisted by hirarchi analytical analysis process (AHP), which involves several sources related to show that the alternative selected is District Sape used as a new autonomous region (DOB).